Potential influence of IS0 9001: 2000 quality management principles on service quality in Kenya’s hotel industry - Shirandula, Duncan; Barsulai, Stella (Current Issues in African Tourism Research, 2017)
In this time of globalization and turbulent economic environment, hotel establishments in the world are required to implement new management approaches in order to provide high quality service. Implementation of quality management principles in Kenyan hotel establishments offers an opportunity to improve on the overall quality of service. This study explored the potential influence of ISO 9001: Quality Management Principleson service quality in the hotel industry in Kenya. The study employed co-relational research design. The target population was 300 employees and 80 middle level managersfrom selected star rated hotels in Nairobi city. Stratified and systematic sampling techniques wereadopted to identify the respondents for the study. Using a ten percent formula, the sample size was determined to be 30 first line employees and 8 middle level managers. Both primary and secondary sources of data were adopted. Structured questionnaires were used to collect primary data from the respondents while secondary data was collected from journals and hotel records. Reliability was measured using the Cronbach‘s Alpha at a level of 0.7%. Inferential and descriptive statisticswere used to analyze data. The findings of the study indicate a relationship between ISO 9001 and service quality (r = 0.5 p<0.001).In order to enhance service quality, recommendations are made to hotels to embrace accreditation under ISO 9001: 2000 Quality Management Systems.
Keywords: ISO; Service quality; Quality Management Principles